Changing the syringe pump: A challenging procedure in critically ill patients. Issue 6 (November 2020) - Elli, Stefano; Mattiussi, Elisa; Bambi, Stefano; Tupputi, Serena; San Fratello, Salvatore; De Nunzio, Angela; D'Auria, Salvatore; Rona, Roberto; Fumagalli, Roberto; Lucchini, Alberto
Introduction: In the literature, the change of a syringe pump is described as a dangerous situation, especially in the case of vasoactive drug administration. Methods: Different variables have been studied (central venous pressure, pump displacement in relation to the patient position, utilization of a stopcock, or a neutral displacement needle-free connector between the syringe and the infusion tubing) to understand their influence on medication administration in terms of backflow or bolus creation when changing the syringe. Results: We performed 576 measurements with different combinations. With respect to all the observations, in comparison with "time zero, " we found the following differences expressed in microliters: 0 (±1) at the plunger opening; 0 (±3) at the syringe extraction from the pump; 0 (±7) at the syringe disconnection from the infusion tubing; 0 (±11) at the syringe reconnection to the infusion tubing; 1 (±7) at the syringe insertion in the pump; 3 (±23) at the plunger closing; 8 (±33) at the stabilization at the maneuver end. Conclusion: The syringe change can be a very critical moment given different influencing variables. Syringe pump position, displaced higher than the patient level, always generates a medication bolus that is higher at the lowering of the central venous pressure value. The presence of a neutral displacement needle-free connector reduces the incidence of boluses. When the pump is placed at the patient level, the presence of neutral displacement needle-free connector reduces the establishment of boluses, even in a central venous pressure of −5 mmHg simulations.